A panoramic view of the strategies for epithelial ovarian cancer: a review of current challenges - Mustafa, Mohd; Habib, Safia; Moinuddin; Singh, Yogendra (International Journal of Basic & Clinical Pharmacology, 2024)
Epithelial ovarian cancer (EOC) remains a formidable challenge in the field of gynecological oncology, accounting for a significant proportion of cancer-related deaths among women worldwide. Despite advances in surgical techniques and chemotherapeutic regimens, the prognosis for patients with advanced-stage disease continues to be dismal, underscoring the urgent need for novel and more effective treatment strategies. This editorial review examines intriguing therapeutic modalities that have the potential to improve treatment outcomes as well as overcome the current difficulties in managing EOC. It presents a brief but comprehensive examination of current research literature about epithelial ovarian cancer, challenges, disease recurrence, molecular complexity, and emerging therapeutic modalities. The importance of gene- and stem-cell therapy in pursuing effective ovarian cancer treatments still holds the platform. While traditional chemotherapy remains crucial for advanced cases, surgical interventions remain pivotal for early-stage patients. Treatment options include innovative DNA polymerase (alpha/delta/epsilon) inhibitors, personalized treatments, and immunotherapies toward advanced cases for quality survival. The challenges posed by epithelial ovarian cancer and late diagnosis necessitate a continuous quest for improved therapeutic options. Emerging approaches such as gene and stem cell therapies show promise in reshaping treatment paradigms. Further exploring localized treatment modalities presents avenues for enhancing improved patient payoff.